A Performance Investigation of a Single Phase Multilevel Inverter Fed Nonlinear Loads for Solar PV Applications - Gnanavel, C.; Rajavelan, M.; Muthukumar, P.; Baldwin Immanuel, T. (International Journal of Engineering and Technology, 2026)
This paper is design and enlargement of eleven multilevel inverter fed nonlinear loads for solar PV applications. First, control the speed of induction motor, to determine the effectiveness of multilevel inverter and its compare. Second, the open loop control of nonlinear loads according to required operation point of the loads the different operation conditions, fast transient response is obtained. The proposed inverter system is compare with R, RL and Induction motor load performance of inverter and to determine the Total Harmonic Distortion (THD). The proposed system verified simulation result are validate and discussed.